Diasporas and development : an assessment of the Irish experience for the Caribbean - Minto, Indianna D. (The Centre for International Governance Innovation WaterlooCA, 2009)
Highlights the lessons of the Irish experience and argues that while the Caribbean's diaspora has the desire to contribute and does help through remittances, there remain a number of challenges to this participation. Sees this as including perceptions of security and stability, establishing the conditions necessary for attracting investment and a lack of confidence in government institutions in the region.